A.V. Dicey and the common law constitutional tradition : a legal turn of mind - Walters, Mark D, 1965- (Cambridge : Cambridge University Press, 2020)
In the common law world, Albert Venn Dicey (1835-1922) is known as the high priest of orthodox constitutional theory, as an ideological and nationalistic positivist. In his analytical coldness, his celebration of sovereign power, and his incessant drive to organize and codify legal rules separate from moral values or political realities, Dicey is an uncanny figure. This book challenges this received view of Dicey. Through a re-examination of his life and his 1885 book Law of the Constitution, the high priest Dicey is defrocked and a more human Dicey steps forward to offer alternative ways of reading his canonical text, who struggled to appreciate law as a form of reasoned discourse that integrates values of legality and authority through methods of ordinary legal interpretation. The result is a unique common law constitutional discourse through which assertions of sovereign power are conditioned by moral aspirations associated with the rule of law.
Introduction -- The Biggest Legal Mind We Have -- Young Dicey in Oxford -- Dicey the Common Lawyer -- Dicey and the Art and Science of Law -- Lectures Introductory to the Law of the Constitution -- Dicey's Legal Constitution -- The Law of Parliamentary Sovereignty -- The Supremacy of Ordinary Law -- Sovereignty and the Spirit of Legality -- Dicey's Administrative Law Blind Spot -- Towards a Discursive Legalism -- The Constitution in the Common Law Tradition -- Appendix : Was Dicey Diceyan?
Title from publisher's bibliographic system (viewed on 15 Jan 2021).
Keywords: Dicey, A. V. -- 1835-1922.; Law teachers -- England -- Biography; Common law -- England; Constitutional law -- Great Britain